2021
DOI: 10.3390/brainsci11050566
|View full text |Cite
|
Sign up to set email alerts
|

Attention and Default Mode Network Assessments of Meditation Experience during Active Cognition and Rest

Abstract: Meditation experience has previously been shown to improve performance on behavioral assessments of attention, but the neural bases of this improvement are unknown. Two prominent, strongly competing networks exist in the human cortex: a dorsal attention network, that is activated during focused attention, and a default mode network, that is suppressed during attentionally demanding tasks. Prior studies suggest that strong anti-correlations between these networks indicate good brain health. In addition, a third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 98 publications
(123 reference statements)
0
10
0
Order By: Relevance
“…A study on meditators found the dynamic interplay between DMN and frontoparietal regions in the alpha band as the meditators transitioned from resting state to one of two different meditations (Marzetti et al, 2014). Meditators have higher anticorrelated DMN-DAN connectivity as compared to healthy controls (Devaney et al, 2021) suggesting meditation as an intervention for maintaining cognitive health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on meditators found the dynamic interplay between DMN and frontoparietal regions in the alpha band as the meditators transitioned from resting state to one of two different meditations (Marzetti et al, 2014). Meditators have higher anticorrelated DMN-DAN connectivity as compared to healthy controls (Devaney et al, 2021) suggesting meditation as an intervention for maintaining cognitive health.…”
Section: Discussionmentioning
confidence: 99%
“…DMN and DAN have been found to be anticorrelated (Fox et al, 2005) wherein cognitively demanding tasks activate the DAN and suppress the DMN (Greicius and Menon, 2004). Studies have found DMN connectivity with other networks to be a biomarker of cognitive health (Falahpour et al, 2016; Kim et al, 2017; Mowinckel et al, 2017; Soares et al, 2017) and expert meditators have a higher DMN-DAN anticorrelation as compared to healthy controls (Devaney et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Alpha power is a characteristic frequency of the brain with relations with the Default Mode Network of the brain 41 . Reduction in the peak alpha amplitudes could also signify decrease in the Default Mode activity of the brain as studies have found reduced mind wandering during meditation 35 and meditators have shown better anticorrelation with the Dorsal Attention Network which suggests better cognitive health 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Alpha power is a characteristic frequency of the brain with relations with the Default Mode Network of the brain 41 . Reduction in the peak alpha amplitudes could also signify decrease in the Default Mode activity of the brain as studies have found reduced mind wandering during meditation 35 and meditators have shown better anticorrelation with the Dorsal Attention Network which suggests better cognitive health 42 . Human theta rhythm characterized by 4-7 Hz oscillations have been linked with various tasks like recognition 43 , spatial navigation [44][45][46] , working memory 43 , episodic memory retrieval 47 and other complex cognitive tasks 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…In the Tantric tradition that is part of Hinduism, sexual energy and the excitement generated in the sacral chakra in the pelvic region, is used to raise “spiritual energy.” The practices of yoga meditation, and some type of Buddhism, also integrate aspects of sensuality and meditation. A number of prior studies have examined the effects of acute meditation practices on brain physiology and functional connectivity ( Fox et al, 2016 ; Hernández et al, 2018 ; Devaney et al, 2021 ). Some of these have been activation studies evaluating brain function during the meditation practice or a task affected by the practice.…”
Section: Introductionmentioning
confidence: 99%